2021
DOI: 10.1002/anie.202016898
|View full text |Cite
|
Sign up to set email alerts
|

B‐Cu‐Zn Gas Diffusion Electrodes for CO2 Electroreduction to C2+ Products at High Current Densities

Abstract: Electroreduction of CO 2 to multi-carbon products has attracted considerable attention as it provides an avenue to high-density renewable energy storage.However,the selectivity and stability under high current densities are rarely reported. Herein, B-doped Cu (B-Cu) and B-Cu-Zn gas diffusion electrodes (GDE) were developed for highly selective and stable CO 2 conversion to C 2+ products at industrially relevant current densities.T he B-Cu GDE exhibited ah igh Faradaic efficiency of 79 %f or C 2+ products forma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(71 citation statements)
references
References 34 publications
(68 reference statements)
1
64
0
Order By: Relevance
“…Further, the catalyst with a composition of 0.5BÀ Cu:0.025Zn exhibited increased FE for ethanol (31 %) and n-propanol (3 %) at À 0.45 V (vs. RHE) with total CD of À 200 mA cm À 2 . [45] In-situ Raman measurements showed that the addition of boron and Zn maintains stability of Cu + species during ECO 2 R resulting in increased ethanol selectively and the long-term stability on BÀ CuÀ Zn, however, the FE of C 2 H 5 OH was decreased at higher Zn loading due to the competing HER and excess CO production by Zn.…”
Section: Composition Of Catalystmentioning
confidence: 99%
See 3 more Smart Citations
“…Further, the catalyst with a composition of 0.5BÀ Cu:0.025Zn exhibited increased FE for ethanol (31 %) and n-propanol (3 %) at À 0.45 V (vs. RHE) with total CD of À 200 mA cm À 2 . [45] In-situ Raman measurements showed that the addition of boron and Zn maintains stability of Cu + species during ECO 2 R resulting in increased ethanol selectively and the long-term stability on BÀ CuÀ Zn, however, the FE of C 2 H 5 OH was decreased at higher Zn loading due to the competing HER and excess CO production by Zn.…”
Section: Composition Of Catalystmentioning
confidence: 99%
“…Although ECO 2 R has many advantages as listed earlier, but there are some challenges also which inhibit the CO 2 electroreduction performance, such as high over-potential (high energy consumption), poor product selectivity, low energy efficiency, and slow kinetics of CO 2 electrochemical reduction reaction, etc.. [19] Therefore, there is a need to develop an electro-catalyst which is highly selective, stable, cheap, and able to produce different chemicals at low over-potential with high rates without the formation of undesirable byproducts. [13,36] Numerous strategies have been developed to synthesize ethanol selective electro-catalysts, e. g. electrochemical deposition, [37][38][39] hydrothermal synthesis, [40] thermal annealing, [41,42] chemical reduction of different metal salts [43][44][45] and soft templating method. [46,47] Most of these methods undergo oxidation step followed by an in-situ reduction to metallic state during ECO 2 R. In this section, the preparation of Table 2.…”
Section: Electrocatalysts For Reduction Of Carbon Dioxide To Ethanolmentioning
confidence: 99%
See 2 more Smart Citations
“…Only recently has acknowledgment of this potentially significant problem been alluded to by Song et al. who employed flakes of zinc as sacrificial cathodes within the structure of their copper particle‐based cathodes 168. Whilst this might present a short‐term solution, this phenomenon is another significant constraint in this challenging process, one that might require a major reconsideration of the viability of utilizing alkali metal cations in alkaline electrolytes.…”
Section: Effects On Ethylene Productionmentioning
confidence: 99%